Penerapan Model Pembelajaran STAD (Student Teams Achievement Divison) Untuk Meningkatkan Hasil Belajar Siswa pada Materi Sejarah Kelas VIII SMPN 3 Srengat Blitar - Wiji Utami; Jani Jani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research is motivated by the fact that the history learning process in schools is often considered boring and less relevant to students' lives. Initial observations at SMPN 3 Srengat Blitar showed that the dominant lecture method makes students less focused, tend to be passive, and learning outcomes are less than optimal. This condition demands learning innovations that can involve students actively and meaningfully. One alternative used is the Student Teams Achievement Division (STAD) cooperative learning model. The focus of this research is to describe the application of the STAD model to improve the learning outcomes of eighth-grade students on the history of the arrival of Western nations to Indonesia. The research objectives include: (1) outlining the steps for implementing the STAD model, (2) identifying supporting and inhibiting factors, and (3) determining the impact of STAD implementation on improving student learning outcomes. The type of research used is descriptive qualitative with a naturalistic approach. Data were collected through observation, interviews, and documentation. The research subjects were eighth-grade students of SMPN 3 Srengat Blitar in the 2023/2024 academic year. The researcher was directly involved in the data collection and analysis process using triangulation techniques to ensure the validity of the findings. The research results show that the implementation of STAD can improve student learning outcomes. Students become more active, motivated, and have a better understanding of the material. The main supporting factors are solid teamwork and the teacher's active role in facilitating learning. Challenges faced include time constraints and students' initial adaptation to the new method. Overall, STAD has proven effective in creating a fun, interactive, and meaningful learning environment for students.